Risk Management Education for Administrative Staff at the Muhammadiyah Regional Leadership Office of the Special Region of Yogyakarta - Gita Danupranata; Siti Dyah Handayani; Farid Setiawan; Guntur Nugroho (PUBLICA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study focuses on the problem of lack of understanding and structured framework regarding operational risk management among administrative staff at the Muhammadiyah Regional Leadership Office of the Special Region of Yogyakarta (PWM DIY). The method used to solve this problem is through a Participatory-Practical approach consisting of three main stages: Cognitive Training (basic understanding of risk management), Skills Training (preparing a spreadsheet-based Risk Register and designing SOPs), and Mitigation Assistance (light infrastructure risk education). The main results of this service showed a significant increase in staff understanding based on a comparison of pre-tests and post-tests, the formation of a formal Administrative Risk Register document, and availability of mini SOPs for office physical risk preparedness. The main conclusion of this activity is that the implementation of a Risk Management System adapted from ISO 31000:2018 has proven effective in increasing the capacity for more accountable, transparent, and professional administrative governance in religious non-profit organizations in line with the achievement of SDG target 16.6.